How the Nitrogen Economy of a Perennial Cereal-Legume Intercrop Affects Productivity: Can Synchrony Be Achieved? - Crews, Timothy E.; Kemp, Laura; Bowden, James H.; Murrell, Ebony G. (Frontiers in Sustainable Food Systems, 2022)
The UN's Sustainable Development goal of Zero Hunger encompasses a holistic set of targets that range from ending hunger by 2030, to increasing environmental sustainability and resilience of food production. Securing and managing soil nutrients remains one of the most basic challenges to growing adequate food while simultaneously protecting biodiversity and the integrity of ecosystems. To achieve these objectives, it is increasingly clear that the management of ecological processes will need to supplant reliance on non-renewable and environmentally damaging inputs. In recent years, progress has been made in developing perennial grain crops that show promise to improve on a range of ecological functions such as efficient nitrogen cycling and soil carbon accretion that tend to be well-developed in natural ecosystems but become compromised following land conversion to row crop agriculture. Here we report on a multi-faceted, 5-year experiment in which intermediate wheatgrass (IWG) (Thinopyrum intermedium), a perennial relative of wheat that is bred to produce the grain Kernza®, was intercropped in alternating rows with the perennial legume alfalfa (Medicago sativa). The performance of the unfertilized intercrop was compared to monocropped IWG treatments, with and without urea-N applications, planted at two row densities such that the intercrop could be interpreted as either an addition or substitution design. Comparisons of relative IWG yields (RYs) in the intercrop with unfertilized monocrops suggest net competitive interactions between alfalfa and IWG in the establishment year, followed by increasing degrees of facilitation over the next 4 years. Evidence from N fertilizer responsiveness, SPAD readings, net N mineralization assays, and N balance calculations suggest that alfalfa contributed to an aggrading pool of soil organic nitrogen over the course of the experiment. Comparisons of grain RYs of intercropped IWG and fertilized IWG monocultures suggest N-limitation in the first half of the experiment, and N sufficiency in the second half. Grain yields in the intercrop did not decline significantly over 5 years in contrast to all IWG monocrop treatments that did significantly decline. This study contributes to a growing literature on approaches to ecological nutrient management that incorporate diversity and perenniality to increase food security and resilience.